ESTABLISHING RATE OF CONVERSION FROM FULL CODE TO DO NOT RESUSCITATE STATUS AMONG LONG-STAY NURSING HOME RESIDENTS. (11th November 2018) - McCreedy, E; Mor, V; Mitchell, S; Loomer, L
Abstract: The purpose of this research is to establish the natural rate at which long-stay nursing home residents switch from being "full code" to "do-not-resuscitate" (DNR) or "do-not-hospitalize" (DNH) status. Data sources included the EHR and the Minimum Data Set. Survival analyses estimated the cumulative probability of switching from full code to DNR or DNH during the 12-month observation window. The study population is NH residents who became long-stay (>90 days) between October 1, 2016 and September 30, 2017. Among residents who were full code when they became long-stay, person-days were calculated from the date the resident became long-stay to the date of a physician order for DNR or DNH. Among 2, 802 residents who became long-stay during observation window, 1, 415 (51%) were full code at baseline, 1, 240 (44%) had orders for DNR or DNH, and 147 (5%) had unclear status. During the 12-month observation, 184 of 1, 415 (13%) full code residents switched to DNR or DNH, 206 (15%) were discharged or died; and 1025 (72%) remained full code. The 1, 415 residents who were full code at baseline accumulated 402, 794 person-days at-risk during the observation window, establishing a natural switching rate of 1.4% per person-month. Being African American and having high family involvement in care were associated with more time spent as full code. Medicare and other funders are currently testing interventions to improve advance care planning at the end of life. Having an understanding of natural switching rates may help researchers and policy-makers evaluate the effectiveness of such interventions.